PENGARUH BUDAYA ORGANISASI DAN SELF EFFICASY TERHADAP KEMAMPUAN MANAJEMEN KONFLIK TARUNA DI LEMDIKLAT AKPOL SEMARANG - Hendrik A.E. Lao; Tri Widada; Merensiana Hale (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
The conflict management ability of cadets in the Educational and Training Institute at the Semarang Police Academic is still low or not optimal. This needs special attention from all parties involved in the Police Academy. Because of the various reasons raised by cadets that they have not maximally practiced conflict management courses and it is only theoretical that cadets get. Therefore, increasing the ability of educators needs to be considered in teaching any material taught to cadets. This research is a quantitative study with a sample size of 28 people. The data collection technique is a closed questionnaire technique, while the data analysis technique uses SPSS 21 to determine the effect of organizational culture, self-efficacy on the conflict management skills of cadets at the Police Academy. The results showed that there was an influence of organizational culture by 28.1%, self-efficacy on conflict management by 49.5%. This shows that conflict management skills can increase if organizational culture and self-efficacy are increased effectively.